2020
DOI: 10.1155/2020/3648941
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness and Urinary Albumin Excretion in Type 2 Diabetic Patients without Retinopathy

Abstract: The role of retinal vasculature’s dysfunction in the physiopathology of Diabetic Retinopathy (DR) has been extensively described. Recently, the existence of a diabetic choroidal vasculopathy has been proposed. The purpose of this study was to compare choroidal thickness (CT) in nondiabetic patients and in type 2 diabetic patients without retinopathy, using EDI SD-OCT. Additionally, considering the diabetic patient group, compare CT in patients with and without microalbuminuria. This retrospective study selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Microalbuminuria was significantly correlated with a reduction in choroidal thickness and volume in diabetic patients without retinopathy [ 28 ]. On the contrary, Oliveira-Ferreira et al [ 18 ] in their retrospective study stated that the SFCT was higher in diabetic patients without DR when compared to nondiabetic patients. Microalbuminuria was accompanied by thickening of the subfoveal and temporal choroid in diabetic patients without DR when compared with normoalbuminuric diabetics and non-diabetics [ 18 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Microalbuminuria was significantly correlated with a reduction in choroidal thickness and volume in diabetic patients without retinopathy [ 28 ]. On the contrary, Oliveira-Ferreira et al [ 18 ] in their retrospective study stated that the SFCT was higher in diabetic patients without DR when compared to nondiabetic patients. Microalbuminuria was accompanied by thickening of the subfoveal and temporal choroid in diabetic patients without DR when compared with normoalbuminuric diabetics and non-diabetics [ 18 ].…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, Oliveira-Ferreira et al [ 18 ] in their retrospective study stated that the SFCT was higher in diabetic patients without DR when compared to nondiabetic patients. Microalbuminuria was accompanied by thickening of the subfoveal and temporal choroid in diabetic patients without DR when compared with normoalbuminuric diabetics and non-diabetics [ 18 ]. These controversial results might be attributed to the manual measurement of CT in specified points rather than obtaining a map.…”
Section: Discussionmentioning
confidence: 91%
“…Oliveira-Ferreira et al compared patients with T2D with normoalbuminuria or microalbuminuria, without DR, with healthy controls, and also found an increase of mean subfoveal CT in diabetics as well as thicker subfoveal CT and temporal CT in patients with T2D with microalbuminuria compared both with controls as normoalbuminuric patients. 24 In contrast, a recent meta-analysis suggested that subfoveal choroidal thickness is thinner in diabetic eyes compared with controls, and that the ratio of Pathophysiology/complications luminal areas (corresponding to the choroidal vascular lumens) is lower in diabetic eyes of patients without clinically detectable DR compared with control eyes. 25 26 Likewise, Ashour et al, in a study whose aim was to understand the effect of microalbuminuria on diabetic choroid, had found that patients with T2D have thinner CT compared with non-diabetic controls.…”
Section: Discussionmentioning
confidence: 94%
“…Oliveira-Ferreira et al compared patients with T2D with normoalbuminuria or microalbuminuria, without DR, with healthy controls, and also found an increase of mean subfoveal CT in diabetics as well as thicker subfoveal CT and temporal CT in patients with T2D with microalbuminuria compared both with controls as normoalbuminuric patients. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Malerbi et al (2018) reported increased subfoveal choroid thickness in T1D with microalbuminuria vs normal UAE [20]. Oliveira-Ferreira et al (2020) also found thicker subfoveal and temporal CT in T2D patients with microalbuminuria compared to diabetics with normal UAE and healthy controls [23]. Increase of CT in the early stages followed by decrease were observed both in T1D as T2D patients [24] , [25].…”
Section: Discussionmentioning
confidence: 97%